Merokok dan anemia: studi pada pasien rawat inap di Rumah Sakit Paru Respira Yogyakarta - Ledy Vinantika; Solikhah Solikhah (Berita Kedokteran Masyarakat (BKM), 2018)
Smoking and anemia: study in hospitalized patients at Respira Lung Hospital, YogyakartaPurpose: This study aimed to explore anemia in hospitalized patients at Respira Lung Hospital in Yogyakarta which includes tuberculosis, nutritional status, age, sex, education, and smoking habits.Methods: A cross-sectional design using secondary data from medical records at Respira Lung Hospital was used in this study. Of all medical records, 90 inpatients in 2017 were taken with consecutive sampling techniques. The Chi-square test was conducted to analyze this study.Results: Patients who had anaemia were 52,2%. The proportion of people who had anaemia in thin people was 1,613 greater than those who are not thin (RP=1,613; 95%CI=1,078-2,414; p=0,031). Disease, age, sex, education, and smoking habits were not significantly related to anaemia. However, pulmonary tuberculosis (TB) (RP=1,395; 95%CI=0,951-2,047); no education (RP=1,257; 95%CI=0,765-2,066); and smoking habits (RP=1,142; 95%CI=0,730-1,785) were risk factors for anaemia in hospitalized patients at Respira Lung Hospital.Conclusions: Nutritional status was significantly associated with anemia, while pulmonary TB, age, gender, education, and smoking habits were not significantly related to anemia. Furthermore, increasing awareness of pulmonary tuberculosis sufferers with poor nutritional status, smoker, and low education was concerned by the health department because it raised the risk of anemia and complication of the disease.